Pembelajaran Ilmu Tajwid dalam Meningkatkan Kualitas Bacaan Al-Qur’an - Chalimatus Sa’dijah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2021)
This paper defote to prove the importance of Ilmu Tajwid in the formation of standard guides and standards in the recitation of the Qur'an. Therefore, this paper seeks to answer a single problem: "Is it true that the recitation of the Qur'an requires the standard standard of Ilmu Tajwid in guaranteeing the quality of qur'anic recitation?" This paper will try to explore a number of rules or guidelines that can be understood from Ilmu Tajwid. From this, then it is necessary to show how the Ilmu Tajwid is implemented in reading the Qur'an. In order to remain fokused on the single problem above, this paper seeks to show empirically in the recitation of the Qur'an carried out by IIQ Jakarta students.Primary data sources come from IIQ Jakarta students and secondary data sources to complete the necessary data. Both primary and secondary data were dug through observation in Ilmu Tajwid learning classes. Dokumenter studies are also needed to understand the learning of Ilmu Tajwid, ranging from planning, implementation, and results achieved. Quesionair is also to capture data on leadership, discipline, motivation and teacher performance. The T-Test was conducted to test the recitation of the Qur'an from Ilmu Tajwid students. The Result This Study the recitation of the Qur'an carried out by IIQ Jakarta students has fulfilled the quality that has been built through the standardization of Tajwid Science. This standardization includes how to ensure a reading is adjusted to students' understanding of Tajwid Science studied in lectures that have been implemented.